Implementation of Pancasila and Citizenship Education in the Pancasila Student Profile Program at Schools - Apeles Lexi Lontoh,; Arif Sobirin Wibowo,; Wua Telly Delly,; Eka Yuliana Rahman,; Joupy G.Z. Mambu5, (Technium Education and Humanities, 2024)
Learning Pancasila and Citizenship Education consistently incorporates Pancasila values into its teachings. By studying this subject, students can grasp their rights and responsibilities as citizens and address issues related to citizenship, such as national unity, maintaining values and norms, human rights, power and politics, a democratic society, Pancasila and the State constitution, and globalization. The Pancasila student profile aims to develop graduates who are both of strong character and highly competent, reinforcing the fundamental values of Pancasila. This study employs a literature review method, sourcing data from books and journals. A literature review involves identifying, evaluating, and interpreting all relevant research findings related to a specific research question, topic, or phenomenon. The implementation of Pancasila and Citizenship Education within the Pancasila student profile in schools focuses on enhancing content related to cooperation, independence, creativity, global diversity, critical thinking, and faith in God Almighty with noble character. These elements are essential features of the Pancasila student profile program and must be practically applied in all school learning activities.